Idiopathic mesenteric phlebosclerosis associated with use of Chinese patent medicine: a case report and literature review - Lv, Li; Gao, Ruo-yu; Yu, Xi-qiu (Frontiers in Medicine, 2025)
Idiopathic Mesenteric Phlebosclerosis Colitis (IMP) is indeed a rare and potentially life-threatening condition characterized by chronic ischemic changes in the colon, primarily due to calcification of the mesenteric veins. This disease is often associated with long-term use of certain herbal medicines, particularly in Asian populations, where its prevalence is notably higher. This report describes a 55-year-old male patient who has been taking Chinese patent medicine orally for an extended period to treat prostatitis. His primary symptom is diarrhea. Imaging studies revealed multiple linear calcifications in the mesenteric veins surrounding the ascending and transverse colon. Colonoscopic findings showed bluish-purple discolored mucosa and multiple ulcers of the colonic and rectal mucosa. Pathological biopsy indicated fibrous tissue proliferation in the mucosal lamina propria and thickening of some blood vessel walls accompanied by hyaline degeneration. Based on clinical presentation, CT, colonoscopy, and histopathological findings, the final diagnosis was confirmed as IMP.